Positive solutions for nonlinear fractional differential equations with boundary conditions involving Riemann-Stieltjes integrals - Jiang, J.; Liu, L.; Wu, Yong Hong (Hindawi Publishing Corporation, 2012)
We consider the existence of positive solutions for a class of nonlinear integral boundary value problems for fractional differential equations. By using some fixed point theorems, the existenceand multiplicity results of positive solutions are obtained. The results obtained in this paperimprove and generalize some well-known results.